Studi Literatur: Efektivitas Media Pembelajaran Berbasis Ispring Suite dan APK2 Builder Untuk Meningkatkan Pembelajaran IPA di Sekolah Dasar - Safitri, Risa; Maharani, Mareta (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to examine the effectiveness of Android-based learning media developed using iSpring Suite and APK2 Builder in improving student learning outcomes in Natural Sciences (IPA) subjects. This literature study collects and analyzes various previous studies that discuss the use of Android technology-based learning media in science education. The main focus of the study is on the comparison of the effectiveness of the two platforms, iSpring Suite and APK2 Builder, in improving conceptual understanding, learning motivation, and student interactivity. Based on the results of the literature review, Android-based media has great potential in improving student understanding through the presentation of more interesting and interactive materials. However, each platform has different advantages and limitations, so the selection of the right platform needs to be adjusted to learning needs and infrastructure limitations. This study provides insight for learning media developers and educators to optimize the use of technology in the science learning process.